2005
DOI: 10.1128/jcm.43.4.1865-1868.2005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evidence for Multiple Host-Specific Strains in the Genus Rhinosporidium

Abstract: The taxonomic relationship of Rhinosporidium seeberi with other organisms remained controversial for over a century. Recently, molecular studies have shown R. seeberi to be a protistal microbe in the newly described class Mesomycetozoea at the animal-fungal boundary. Phylogenetic analyses of R. seeberi using 18S smallsubunit (SSU) rRNA genes from several hosts suggested Rhinosporidium as a monotypic genus. To test this hypothesis, the internal transcribed spacer 1 (ITS1), 5.8S, and ITS2 from eight humans, two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 11 publications
2
22
0
Order By: Relevance
“…Conversely, some histochemical analyses found that these vesicles contain lipidic and proteinaceous elements (Arseculeratne, 2002;Bader & Grueber, 1970;Vanbreuseghem, 1973), a finding that agrees with the position of Ashworth (1924) and Easley et al (1986). Furthermore, our data and other studies showed that the nuclei of R. seeberi are~2-4 mm in diameter (Easley et al, 1986;Thianprasit & Thagerngpol, 1989;Kennedy et al, 1995;Pereira et al, 2005;Savino & Margo, 1983;Vanbreuseghem, 1973;Vilela & Mendoza, 2012), thus the presence of a nucleus inside a 0.5-3.0 mm-diameter vesicle is highly questionable. Besides, there is not a single example of a eukaryotic pathogen releasing their nucleated progeny without a protective cell wall.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Conversely, some histochemical analyses found that these vesicles contain lipidic and proteinaceous elements (Arseculeratne, 2002;Bader & Grueber, 1970;Vanbreuseghem, 1973), a finding that agrees with the position of Ashworth (1924) and Easley et al (1986). Furthermore, our data and other studies showed that the nuclei of R. seeberi are~2-4 mm in diameter (Easley et al, 1986;Thianprasit & Thagerngpol, 1989;Kennedy et al, 1995;Pereira et al, 2005;Savino & Margo, 1983;Vanbreuseghem, 1973;Vilela & Mendoza, 2012), thus the presence of a nucleus inside a 0.5-3.0 mm-diameter vesicle is highly questionable. Besides, there is not a single example of a eukaryotic pathogen releasing their nucleated progeny without a protective cell wall.…”
Section: Discussionsupporting
confidence: 62%
“…According to our observations and those recorded by others (Ashworth, 1924;Kannan-Kutty & Teh, 1974Kennedy et al, 1995;Mendoza et al, 2002;Thianprasit & Thagerngpol, 1989;Vanbreuseghem, 1973), each endoconidium possesses a single nucleus and maintains its cell wall integrity at all times (Pereira et al, 2005;Vilela & Mendoza, 2012), a concept that is in sharp contrast with the spore-morulae hypothesis. Conversely, believe that the concentric 0.5-1.5 mm diameter ring structures, also termed laminated bodies (LB) and frequently encountered in EM preparations, are involved in the development of endoconidia.…”
Section: Discussionsupporting
confidence: 42%
See 2 more Smart Citations
“…The etiologic pathogen organism causes similar infections in amphibians and fish (414). Another molecular work has demonstrated evidence that R. seeberi may have host-specific strains (eg, human vs dog versus swan) (415). Humans generally acquire the infection by contact of the nasal mucosa with infectious material when bathing in ponds contaminated by animal feces (416).…”
Section: Zoonotic Parasitic Protozoans (Protozooses)mentioning
confidence: 99%